2011
DOI: 10.1111/j.1742-4658.2011.08025.x
|View full text |Cite
|
Sign up to set email alerts
|

α‐enolase: a promising therapeutic and diagnostic tumor target

Abstract: α‐enolase (ENOA) is a metabolic enzyme involved in the synthesis of pyruvate. It also acts as a plasminogen receptor and thus mediates activation of plasmin and extracellular matrix degradation. In tumor cells, ΕΝΟΑ is upregulated and supports anaerobic proliferation (Warburg effect), it is expressed at the cell surface, where it promotes cancer invasion, and is subjected to a specific array of post‐translational modifications, namely acetylation, methylation and phosphorylation. Both ENOA overexpression and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
227
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 227 publications
(235 citation statements)
references
References 125 publications
(161 reference statements)
4
227
3
1
Order By: Relevance
“…In line with these considerations, high levels of ENO-1 were found in many types of cancer, including head, neck, breast, and lung cancer (44). High levels of ENO-1 in cancer cells correlate with cancer progression and a poor clinical outcome of the affected patients (12). Ectopic overexpression of ENO-1 promotes cell proliferation, migration, invasion, and colony formation, thereby contributing to metastasis formation (19,21,45).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…In line with these considerations, high levels of ENO-1 were found in many types of cancer, including head, neck, breast, and lung cancer (44). High levels of ENO-1 in cancer cells correlate with cancer progression and a poor clinical outcome of the affected patients (12). Ectopic overexpression of ENO-1 promotes cell proliferation, migration, invasion, and colony formation, thereby contributing to metastasis formation (19,21,45).…”
Section: Discussionmentioning
confidence: 77%
“…Enolase-1 is a glycolytic enzyme primarily localized in the cytoplasm of prokaryotic and eukaryotic cells (12). However, under stimulatory conditions, ENO-1 can be translocated to the cell surface, where it acts as a PLG receptor (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 In the cytoplasm, ENO1 acts as a glycolytic enzyme, whereas on the membrane it acts as a plasminogen receptor and plays an important role in cell migration. 6,7 We have shown that patients with PDA with autoantibodies to ENO1 also present an ENO1-specific T-cell response that is not observed in patients with no ENO1 autoantibodies. On transfer into immunocompromised mice, ENO1-specific T cells inhibit the growth of xenotransplanted human pancreatic tumors.…”
mentioning
confidence: 99%
“…Recent studies have revealed that ENO1 can be detected in many prokaryotic and eukaryotic cells, and localized in cytoplasm, cell surface and nucleus of various mammalian cells to possibly mediate distinct functions (Liu et al, 2007). ENO1 gene up-regulation in mRNA and/or protein levels have been observed in several tumors, including brain, breast, cervix, colon, eye, and so on (Liu et al, 2007;Capello et al, 2011).…”
Section: Resultsmentioning
confidence: 99%